Productivity optimization in the electronics industry using simulation-based modeling approach - Tamanna Kamal; S M Atikur Rahman (International Journal of Research in Industrial Engineering)
This study explores productivity optimization in the electronics industry using a simulation-based modeling approach. With growing demand and competition, electronics manufacturers face the challenge of balancing production speed, quality, and cost. Simulation-based modeling provides a solution by enabling a virtual replication of manufacturing processes, allowing for scenario testing without disrupting actual operations. By implementing this approach, critical factors such as resource allocation, machine utilization, and process flow were examined, identifying bottlenecks and inefficiencies. This study specifically used discrete-event simulation to model production lines and test optimization strategies under various conditions, including shifts in demand, machine maintenance schedules, and workforce availability. Results indicated a measurable improvement in production throughput and utilization rates, while delay times were significantly reduced. By adopting a simulation-based approach, the electronics industry can enhance decision-making accuracy, minimize downtime, and increase overall productivity. This method not only provides real-time insights for ongoing operations but also offers a cost-effective tool for long-term strategic planning and continuous process improvement.